Alteration of miR-21, miR-433 and miR-590 tissue expression related to the TGF-β signaling pathway in ulcerative colitis patients. (3rd September 2022) - Naghdalipour, Mehri; Moradi, Nariman; Fadaei, Reza; Rezghi Barez, Shekufe; Sayyahfar, Shirin; Mokhtare, Marjan; Fard, Toktam Kazemi; Fallah, Soudabeh; Esteghamati, Aboulreza
Abstract: Ulcerative colitis (UC) is an inflammatory disease, and studies have suggested a role for TGF-β signalling pathway in the pathogenesis of UC. In the present study, we evaluated expression of TGF-β signalling genes and their regulatory microRNAs in patients with UC and control subjects. The expression of TGF-β1, SMAD2, SMAD3, miR-21, miR-101, miR-433, and miR-590 were evaluated using real-time PCR in biopsy samples of the patients and controls. Results showed increased expression of TGF-β1 and SMAD3 in the patients compared to controls. In addition, miR-21 and miR-433 were found to be higher in the patients compared to controls; however, miR-590 was found to be lower. Moreover, miR-433 was demonstrated to have positive correlation with SMAD3 and TGF-β while miR-21 was positively correlated with TGF-β1. MiR-590 was negatively correlated with SMAD2 and SMAD3. Results of the present study suggested a role for TGF-β signalling pathway related microRNAs in pathogenesis of UC.